2020
DOI: 10.1097/fch.0000000000000254
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Perceived Racial Discrimination and Hypertension in a Low-Income, Racially Integrated Urban Community

Abstract: We examined the association between perceived racial discrimination and hypertension among African Americans and whites who live in a low-income, racially integrated, urban community. Hypertension was defined as having a systolic blood pressure 140 mm Hg or more, a diastolic blood pressure 90 mm Hg or more, or taking antihypertensive medication(s). Perceived racial discrimination was based on self-reported responses of experiencing racial discrimination in various settings. Using modified Poisson multivariable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…The IOM Report focused on health care disparities and highlighted the role interpersonal racism can have on health outcomes for members of minoritized groups (25). These reports and others (9,(27)(28)(29)(30)(31)(32)(33)(34)(35) have led to a more robust focus on population health over the last few decades that has included a renewed interest in the impact of racism and social factors, such as poverty on clinical outcomes (1,33).…”
Section: Poverty and Health Disparities A Historical Perspectivementioning
confidence: 99%
“…The IOM Report focused on health care disparities and highlighted the role interpersonal racism can have on health outcomes for members of minoritized groups (25). These reports and others (9,(27)(28)(29)(30)(31)(32)(33)(34)(35) have led to a more robust focus on population health over the last few decades that has included a renewed interest in the impact of racism and social factors, such as poverty on clinical outcomes (1,33).…”
Section: Poverty and Health Disparities A Historical Perspectivementioning
confidence: 99%
“…Our novel results highlighting educational attainment as a potential modifier of RED-hypertension within Black women are plausible when considering prior discrimination literature . Prior studies have demonstrated links between RED and hypertension across multiethnic populations and varying age ranges . Studies have also shown that health benefits related to higher educational attainment are not equitable among Black and Latina compared to White adults, which is likely related to the pervasiveness of structural racism and other forms of discrimination faced by minoritized racial and ethnic groups .…”
Section: Discussionmentioning
confidence: 50%
“…23 Prior studies have demonstrated links between RED and hypertension across multiethnic populations and varying age ranges. 6,18,25,26,30,31,45 Studies have also shown that health benefits related to higher educational attainment are not equitable among Black and Latina compared to White adults, which is likely related to the pervasiveness of structural racism and other forms of discrimination faced by minoritized racial and ethnic groups. 9,[19][20][21][22][23]46,47 Our findings of EM by educational attainment for everyday RED but not major RED add valuable insights into RED's health impacts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While some argue that race is a “social construct and not a defining biology [ 122 ],” African Americans and other people of African descent have a higher incidence of hypertension and related comorbidities compared to White individuals, with several identifiable genes helping to potentially account for racial differences regarding hypertension [ 123 ]. Regarding perceived racial discrimination and hypertension, the reported association is variable [ [124] , [125] , [126] , [127] , [128] ], with challenges regarding methodology of analyses, and likely most applicable when examined on an individual basis. Obesity also is also pathogenic among Latine individuals [ 129 ], who have high rates of cardiometabolic risk factors such as obesity, high blood glucose, high blood lipids, and high blood pressure [ 130 ].…”
Section: Genetics Epigenetics Sex Gender Race Ethnicity Obesity and H...mentioning
confidence: 99%